Physical activity and well-being of students of faculties medical and non-medical services during the Covid-19 pandemic - Sochacka, Magdalena; Zdziarski, Krzysztof (Journal of Education, Health and Sport, 2022)
Physical activity has a positive effect on the human body, well-being and mental health. This is confirmed by the results of studies which show that regular physical exercise has a beneficial effect not only on the cardiovascular, muscular and nervous systems, as well as on mental well-being. The Covid-19 pandemic, which affected society as a whole, changed our lives. The pandemic has a social and economic scope, increasing the number of stressful situations that affect well-being. Aim of the research: The aim of the undertaken research was to check the level of physical activity and well-being of medical and non-medical students during the pandemic. Material and methods: The research used the method of diagnostic survey, with the use of the proprietary questionnaire and the International Physical Activity Questionnaire (IPAQ) as well as a 36-point Health Survey were used. The research group consisted of students of medical and non-medical faculties. Results: The research confirmed a decrease in physical activity and a change in well-being in students of both faculties. The vast majority of students (80%) noticed a change in well-being during the pandemic. Half of the respondents (50%) undertake physical activity to improve their well-being, and over 60% of the students declared that physical activity helps them maintain their well-being during the pandemic. Conclusions: The results of the conducted research indicate a negative impact of the pandemic on the physical activity and well-being of the respondents. There was a strong correlation between physical activity and the well-being of research participants. The greatest decrease in physical activity was observed in medical students (52.08%). On the other hand, students of non-medical faculties (54.17%) showed a lower level of well-being, and higher medical students (45.83%). It is advisable to take preventive measures through active physical activity in order to eliminate the negative effects of the pandemic.